Between Conformity and Transgression: Gender Expression in Virginia Woolf’s Orlando - Bode, Alicia (Satura, 2026)
Virginia Woolf’s presentation of Orlando in the novel Orlando: A Biography allows for a wide range of interpretations of gender and identity and therefore lends itself to various approaches within Queer Theory. While most analyses focus on the protagonist's efforts of deconstructing gendered expectations through subversive practices, this paper also highlights the importance of Orlando's deliberate efforts of passing as male or female. By combining Judith Butler's ideas on gender performativity with the framework of passing, a close textual analysis of the gendered codes regarding dress, behavior, and societal expectations portrayed in the novel reveals how both conformity and nonconforming strategies expose the performative nature of Orlando's gender. Consequently, interpreting these insights against the backdrop of a fluid, androgynous understanding of identity shows how Orlando does not only represent a significant example of breaking gender essentialism and highlighting its performative nature, but also anticipates modern views expanding beyond the gender binary.